'Belvedere' office tower Rotterdam: structural design of a sloping hybrid high-rise. (15th August 2007) - Vambersky, J.N.J.A.
The ambitions of architects to realise exciting designs that challenge gravity and 'defy' the laws of nature are never-ending. An example is the 100 m high sloping office tower 'Belvedere' in Rotterdam, designed by the architect Renzo Piano. The design process, concepts, alternatives, final solutions and detailing of this architecturally appealing building are discussed in this paper, to illustrate the value that structural design and hybrid structures can have.